2014
DOI: 10.1111/cas.12461
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA UCA1 promotes glycolysis by upregulating hexokinase 2 through the mTOR–STAT3/microRNA143 pathway

Abstract: Cancer cells preferentially metabolize glucose through aerobic glycolysis, a phenomenon known as the Warburg effect. Emerging evidence has shown that long non-coding RNAs (lncRNAs) act as key regulators of multiple cancers. However, it remains largely unexplored whether and how lncRNA regulates glucose metabolism in cancer cells. In this study, we show that lncRNA UCA1 promotes glycolysis in bladder cancer cells, and that UCA1-induced hexokinase 2 (HK2) functions as an important mediator in this process. We fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
172
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 222 publications
(183 citation statements)
references
References 29 publications
11
172
0
Order By: Relevance
“…There was no significant difference for PKM2 mRNA in the breast cancer with miR-122-5p or the miRNA control transfection, but, PKM2 protein showed down-regulation in the cells. HK2 was regulated by miR-143 [24], miR-155 [25], miR-199a-5p [26], miR-29b [27,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], miR-140-5p in various cancers like bladder cancer, liver cancer and prostate cancer. LDHA was regulated by miR-383, miR34a, miR-122, miR-30a-5p and other miRNAs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference for PKM2 mRNA in the breast cancer with miR-122-5p or the miRNA control transfection, but, PKM2 protein showed down-regulation in the cells. HK2 was regulated by miR-143 [24], miR-155 [25], miR-199a-5p [26], miR-29b [27,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], miR-140-5p in various cancers like bladder cancer, liver cancer and prostate cancer. LDHA was regulated by miR-383, miR34a, miR-122, miR-30a-5p and other miRNAs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect is controlled by key glycolytic enzymes including hexokinase (HK), phosphofructokinase (PFK), pyruvate kinase (PK), and lactate dehydrogenase (LDH) [8]. Lately, long non-coding RNAs have been identified as a class of crucial regulators of the Warburg effect [9,10]. However, the detailed lncRNA regulatory network modulated by 20(S)-Rg3 to prevent the Warburg effect in ovarian cancer cells has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…UCA1 promotes BC progression through the PI3K/Akt/ CREB pathway [9], enhances BC migration and invasion by the miR-145/FSCN1/Zeb1/Zeb2 network [10], and is involved in regulation of the Warburg effect through the mTOR/STAT3/ miR-143 /HK2 signaling pathway [11]; these findings strongly demonstrate that UCA1 acts as an oncogene in BC development. The results showed that UCA1 participates in regulation of the Warburg effect in BC.…”
Section: Introductionmentioning
confidence: 99%